Analysis of the Potential of Lubuk Larangan Local Wisdom in Science Learning in Junior High Schools - Zaldy, Ari; Solihat, Rini; Riandi, Riandi; Firman, Harry (Unnes Science Education Journal, 2021)
Lubuk Larangan is an area in a river restricted by the community, which must not be disturbed and is forbidden for fishing. It is in Rantau Keloyang District, Muara Bungo Regency, Jambi Province. The local wisdom of Lubuk Larangan has the potential to bring contextual science learning to conserve the environment based on customary regulations for sustainable development. This study aims to determine the potential of Lubuk Larangan area as a source of science learning. Using descriptive exploratory method, the data were obtained from the interviews with Datuk Rio, a traditional leader and science teacher at SMP Negeri 1 Pelepat Ilir. Data collection techniques included observation, interview, and documentation. The findings indicate that several basic competencies are suitable for science education with the material about Lubuk Larangan, namely analyzing the occurrence of environmental pollution and its impact on the ecosystem (KD 3.8); Lubuk Larangan can be developed in learning media such as modules, assessments, and practical activities; Lubuk Larangan can be integrated into science learning to instill education for sustainable development competencies, especially for action on climate. Based on this study, in general, science learning can be linked to local wisdom of Lubuk Larangan according to learning indicators that refer to education for sustainable development.